Identifying Quantitative Trait Loci and Candidate Genes Conferring Resistance to Soybean Mosaic Virus SC7 by Quantitative Trait Loci-Sequencing in Soybean - Zhang, Yong; Song, Jiling; Wang, Lei; Yang, Mengping; Hu, Kaifeng; Li, Weiwei; Sun, Xuhong; Xue, Hong; Dong, Quanzhong; Zhang, Mingming; Lou, Shubao; Yang, Xingyong; et al. (Frontiers in Plant Science, 2022)
Soybean mosaic virus (SMV) is detrimental to soybean (Glycine max) breeding, seed quality, and yield worldwide. Improving the basic resistance of host plants is the most effective and economical method to reduce damage from SMV. Therefore, it is necessary to identify and clone novel SMV resistance genes. Here, we report the characterization two soybean cultivars, DN50 and XQD, with different levels of resistance to SMV. Compared with XQD, DN50 exhibits enhanced resistance to the SMV strain SC7. By combining bulked-segregant analysis (BSA)-seq and fine-mapping, we identified a novel resistance locus, RSMV-11, spanning an approximately 207-kb region on chromosome 11 and containing 25 annotated genes in the reference Williams 82 genome. Of these genes, we identified eleven with nonsynonymous single-nucleotide polymorphisms (SNPs) or InDels in their coding regions between two parents. One gene, GmMATE68 (Glyma.11G028900), harbored a frameshift mutation. GmMATE68 encodes a multidrug and toxic compound extrusion (MATE) transporter that is expressed in all soybean tissues and is induced by SC7. Given that MATE transporter families have been reported to be linked with plant disease resistance, we suggest that GmMATE68 is responsible for SC7 resistance in DN50. Our results reveal a novel SMV-resistance locus, improving understanding of the genetics of soybean disease resistance and providing a potential new tool for marker-assisted selection breeding in soybean.